1989
DOI: 10.1099/00221287-135-5-1201
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Stimulation of the White-Opaque Transition of Candida albicans by Ultraviolet Irradiation

Abstract: 1201Most strains of Candida albicans are capable of switching spontaneously and at high frequency between a number of phenotypes distinguishable by colony morphology. The switching frequency of Candida albicans strain WO-1 between two predominant phenotypes, 'white' and 'opaque', and a minor phenotype, 'fuzzy', increased dramatically with low doses of ultraviolet irradiation that killed less than 20% of the population. The ultraviolet irradiation effect continued to be expressed over many generations as eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 17 publications
1
51
0
Order By: Relevance
“…This model suggests that most, if not all, stressful environments could potentially induce white-opaque switching by inhibiting rates of cell growth. It also has important implications for other studies on phenotypic switching, as changes in switching frequencies previously observed (e.g., in response to UV irradiation; Morrow et al, 1989) may simply be due to indirect effects of the test conditions on cell generation times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model suggests that most, if not all, stressful environments could potentially induce white-opaque switching by inhibiting rates of cell growth. It also has important implications for other studies on phenotypic switching, as changes in switching frequencies previously observed (e.g., in response to UV irradiation; Morrow et al, 1989) may simply be due to indirect effects of the test conditions on cell generation times.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that exogenous factors, such as UV irradiation, increase switching from white to opaque in C. albicans (Morrow et al, 1989;Kolotila and Diamond, 1990). We hypothesized that white-opaque switching may be induced as part of a general response to cell stress in white cells; therefore, we examined whether other types of genotoxic stress could induce switching to opaque.…”
Section: Genotoxic Stress Induces White-opaque Switching In C Albicansmentioning
confidence: 99%
“…Various genetic mechanisms have been invoked to explain the molecular basis of phenotypic transitions in C. albicans (Morrow et al, 1989;Pomts et al, 1987;Rustchenko-Bulgac et al, 1990;Scherer & Stevens, 1988;Slutsky et al, 1985;Sol1 et al, 1987;Suzuki et al, 1989) Our results suggest that some environmental conditions (i.e. the growth medium and/or the incubation temperature) may differentially affect expression of a set of genes (which among other possibilities, may change the activity of enzymes that synthesize wall components) responsible for the manifestation of differ- Table 3), cells were inoculated into liquid YPD medium and rotated on a gyratory incubator (250 r.p.m.)…”
Section: Discussionmentioning
confidence: 99%
“…The cotton end of each swab was inserted into 0.5 ml sterile water in a polypropylene test tube and mixed vigorously for 30 s with a vortex mixer. A 0.15 ml sample of the swab wash was spread onto each of two agar plates containing supplemented Lee's medium (Lee et al, 1975;Morrow et al, 1989) and incubated for 7 days at 25 uC (Vargas et al, 2000). The plates were verified for the different phenotypes such as smooth white, irregular wrinkle, star, ring, myceliated and heavily myceliated.…”
Section: Virulence Factorsmentioning
confidence: 99%